Determinants of financial distress based on accounting, ownership, market and macroeconomic - Senima, Teklaudi Kurniati; Bertuah, Eka (Enrichment : Journal of Management, 2023)
Research was conducted to determine factors that can predict financial distress in Tourism, Restaurant and Hotel sector companies listed on the Indonesia Stock Exchange. The variables used in this study are DER, ROA, ROE, NPM, WCTA, TATO, CR, Managerial Ownership, PER, Inflation. The research uses logistic regression analysis to find which variables can determine which companies experience financial failure and do not experience financial failure. The results showed that the ratios that were able to distinguish distress and non-distressed companies were NPM, WCTA and Managerial Ownership